Chlorophyll-a modulation in the Arabian Gulf using two decades of merged ocean-color data - Shafeeque, Muhammad; Saleem, Abdul Azeez; Chaitanya, Akurathi V. S.; Abdulla, C. P.; Lateef, Salim; Albert, Jiya (Frontiers in Marine Science, 2025)
IntroductionThe Arabian Gulf (Gulf) is a dynamic marine ecosystem in which phytoplankton productivity, indicated by Chlorophyll-a (Chl-a), is strongly affected by environmental and climatic variables. Understanding the spatiotemporal variability of Chl-a and its driving environmental factors is critical for assessing primary productivity and ecosystem dynamics of the Gulf.MethodsThis study investigated the long-term Chl-a variability and its dynamic response to environmental variables in the Gulf using two decades (2003 to 2023) of Chl-a data from merged multi-sensor Ocean Colour Climate Change Initiative. We adopted an integrated approach that includes climatology, multivariate statistical analysis, interannual variability and trend analysis to evaluate Chl-a variability and identify its dominant drivers.ResultsSeasonal climatology exhibited a marked winter bloom driven by convective mixing and nutrient replenishment, followed by a summer decline due to strong stratification. Box average analysis using correlogram and principal component analysis for selected regions revealed distinct regional patterns, with the northern and central Gulf showing higher variability. The results further highlighted sea surface temperature (SST), sea surface salinity, photosynthetically available radiation and wind speed as primary drivers of Chl-a variability in the Gulf. The interannual variability of Chl-a peaks along the central eastern Gulf in winter and central western Gulf during summer, highlighting regional heterogeneity in phytoplankton dynamics. Long-term spatial trend analysis of Chl-a, net primary productivity (NPP) and SST indicated overall decreasing trend in Chl-a and NPP, particularly along the north and eastern coasts of the Gulf; and warming SST in the northern and central Gulf.DiscussionThe results indicate the requirement of further research on the complex interplay between physical and biogeochemical factors, and anthropogenic influences on Chl-a distribution, which can help future monitoring and predictive ecosystem models for the Gulf under changing climate conditions.